Multiplex PCR for detection of virulence markers of Vibrio vulnificus. (4th February 2015) - Bier, N.; Diescher, S.; Strauch, E.
Abstract Vibrio vulnificus is a Gram‐negative pathogen found in coastal and estuarine waters worldwide that can cause life threatening diseases. Characterization of the vcg (virulence correlated gene) or 16S rRNA alleles is used to distinguish virulent (clinical (C)‐type) from presumably avirulent (environmental (E)‐type) strains. However, some studies reported a significant number of clinical strains belonging to the E‐type. In recent years more potential virulence markers have been identified, that are useful for the identification of potentially pathogenic isolates of the E‐type. In this study, we successfully combined detection of pathogenicity region XII, nanA and a mannitol fermentation operon with the virulence associated alleles of the 16S rRNA and vcg genes in one multiplex PCR. Additionally, toxR primers for species confirmation and internal amplification control were included. Validation of multiplex amplification was performed with a total of 132 bacterial strains, including V. vulnificus (n = 71), other Vibrionaceae (n = 50) and non‐Vibrio isolates (n = 11). Multiplex PCR showed reliable amplification of four of the five virulence markers with a high sensitivity and specificity. Amplification of the 16S rRNA type B allele was not completely reliable with conventional PCR assays, however, the positive predictive value of this marker was 100 %. Significance and Impact of the Study A multiplex PCR for simultaneous detection and characterization of potentially virulent strains of Vibrio vulnificus was developed and validated. Monitoring programs will benefit from this cost and time effective method when screening large strain collections. Application of the multiplex PCR simplifies determination of risks emanating from V. vulnificus in recreational waters or mussel primary production.